Nuclear Migration: An Indicator of Plant Salinity Tolerance in vitro - Elmaghrabi, Adel M.; Francis, Dennis; Rogers, Hilary J.; Ochatt, Sergio J. (Frontiers in Plant Science, 2019)
In order to understand the mechanisms underlying acquisition of tolerance to salinity, we recently produced callus tissues of tobacco and Medicago truncatula resistant to NaCl-induced salt stress following application of a step-up recurrent selection method. The effects of salinity on cell size are known, but those on cell morphometry including cell and nuclear surface area and position of nuclei within salt stress resistant cells were never studied before. This work fills that gap, using suspension cultured cells of M. truncatula A17 initiated from callus, and the Nicotiana tabacum BY-2 cell line resistant to increasing NaCl concentrations up to 150 mM NaCl. The surface area of salinity resistant cells of Medicago truncatula A17 and Nicotiana tabacum BY2 and their nuclei, produced by step-up recurrent selection, were reduced, and cells elongated as NaCl increased, but these parameters proved to be unreliable in explaining cell survival and growth at high NaCl. Conversely, nuclei of resistant cells migrated from the centre to the periphery of the cytoplasm close to the walls. Nuclear marginalisation was for the first time observed as a result of salt stress in plant cells, and could be a novel helpful morphological marker of acquisition of salinity tolerance.